2000
DOI: 10.1001/jama.283.10.1311
|View full text |Cite
|
Sign up to set email alerts
|

Extraimmunization Among US Children

Abstract: These data indicate that extraimmunization can be costly. The challenge is to reduce extraimmunization without interfering with more important efforts to combat underimmunization. Improvements in immunization record keeping and sharing practices may help reduce extraimmunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 10 publications
1
35
0
Order By: Relevance
“…[7] Other study analyzed the frequency of extra-immunization doses among US children and found that 21% of children received extraimmunization doses, which resulted in excess annual costs of $26.5 million. [4] Finally, immunization compliance levels could be increased up to 30% by avoiding missed and late immunization doses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] Other study analyzed the frequency of extra-immunization doses among US children and found that 21% of children received extraimmunization doses, which resulted in excess annual costs of $26.5 million. [4] Finally, immunization compliance levels could be increased up to 30% by avoiding missed and late immunization doses.…”
Section: Resultsmentioning
confidence: 99%
“…The maintenance of highest immunization rate also important to decrease infection transmissions and disease control or elimination. [2][3][4][5][6] Vaccines administration at an appropriate vaccination time is necessary to build immune response before pediatric being infected or exposed to vaccine's preventive infectious disease. development in the last century, but the immunization system is still imperfect because there are many countries have unvaccinated pediatrics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Feikema and colleagues estimated the United States wastes $26.5 million per annum on unnecessary vaccines given to infants between 19 and 35 months. 10 The international savings could be valuably redirected to address low vaccine uptake in target population groups.…”
Section: Introductionmentioning
confidence: 99%
“…5 Furthermore, evidence suggests that 10% to 20% of young children receive ≥1 unnecessary, extra immunization. [6][7][8] Fragmentation of immunization records leads to lack of timely, accurate, and complete immunization data at the point of care and can exacerbate both these problems. 6, 9-11 At the practice or organizational level, incomplete immunization records may also adversely affect immunizationrelated quality measures such as completion of the primary immunization series.…”
mentioning
confidence: 99%